Impulse waves generated by snow avalanches: Momentum and energy transfer to a water body. Issue 12 (20th December 2016) - Zitti, Gianluca; Ancey, Christophe; Postacchini, Matteo; Brocchini, Maurizio
Abstract: When a snow avalanche enters a body of water, it creates an impulse wave whose effects may be catastrophic. Assessing the risk posed by such events requires estimates of the wave's features. Empirical equations have been developed for this purpose in the context of landslides and rock avalanches. Despite the density difference between snow and rock, these equations are also used in avalanche protection engineering. We developed a theoretical model which describes the momentum transfers between the particle and water phases of such events. Scaling analysis showed that these momentum transfers were controlled by a number of dimensionless parameters. Approximate solutions could be worked out by aggregating the dimensionless numbers into a single dimensionless group, which then made it possible to reduce the system's degree of freedom. We carried out experiments that mimicked a snow avalanche striking a reservoir. A lightweight granular material was used as a substitute for snow. The setup was devised so as to satisfy the Froude similarity criterion between the real‐world and laboratory scenarios. Our experiments in a water channel showed that the numerical solutions underestimated wave amplitude by a factor of 2 on average. We also compared our experimental data with those obtained by Heller and Hager (2010), who used the same relative particle density as in our runs, but at higher slide Froude numbers. Key Points: Snow avalanches can create catastrophic impulse waves when striking a water basin Snow avalanches create waves whose amplitude is smaller by a factor of 2 than the amplitude generated by aerial landslides Lower impact velocities and buoyancy forces explain the discrepancies between avalanches and landslides